Zgodbe z obrobja - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 2001)
The article analyses the memories published in the collection "That's how we lived - Biographies of Carinthian Slovenes 1-5" (Klagenfurt, 1993-1997). The author dedicates special attention to the sexual and spatial division of labour, pregnancy, delivery, pregnant women's work, motherhood, children, child care and sexual education. These themes are, however, not discussed in the symbolical language of beliefs, traditions and customs, but in the actual language of the contemporary living conditions
Keywords: Carinthian Slovenes; koroški Slovenci; zamejski Slovenci; Koroška; Austria; Avstrija; ethnology; etnologija; položaj žensk; življenjske zgodbe; materinstvo